Coherent motion and anomalous transport properties of exciton and hole polarons with intrinsic vibrationa - Ratner, A.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
It is shown that intrinsic vibrational degrees of freedom, inherent in two-atom exciton and hole polarons, drastically affect their transport properties in wide-band dielectrics (rare-gas solids and alkali halides). A fast excitonic energy transport and a comparatively high hole mobility, experimentally observed and attributed to two-site polarons tightly bound with the lattice, cannot be explained by the conventional theory of small-radius polarons that predicts their negligibly weak diffusion, exponentially small in the ratio of the binding energy to temperature. The theory, developed below with allowance for the intrinsic vibrational structure of two-site polarons describes qualitatively a large relevant set of experimental data which seem anomalous from the viewpoint of the conventional theory.